CHARACTERIZATION OF GELS CONTAINING PECTIN AND OPTIMIZATION OF GEL PRODUCTION BY TAGUCHI METHOD IN FOOD INDUSTRY - Sagir, S.; Acarali, N.; Durak, M. Z. (PLAPIQUI(UNS-CONICET), 2019)
The objective of this research was to optimize the gel production by Taguchi Method as an optimization method and characterize gels by using attenuated total reflectance Fourier transform infrared (ATR - FTIR) and Raman spectroscopy. The statistical method results were obtained and analyzed comparatively in terms of improving both cost and quality for determination of optimum process parameters. This optimization method uses the S/N ratio as a measure of quality characteristics deviating from or nearing to the desired values. This method is expected to serve as an alternative to the conventional optimization method. Clear discrimination and classification of all the studied gel products containing pectin were achieved by hierarchical cluster. As a result, the gels produced could be evaluated in food products such as ice cream, milk dessert or other gelatin containing products such as pharmaceuticals and cosmetics.
Keywords: Pectin; Gels; Raman; FTIR; Taguchi; PORCINE GELATINS; BOVINE; DIFFERENTIATION; HYDROCOLLOIDS; CHALLENGES; Engineering